Titanium–Tissue Interface Reaction and Its Control With Surface Treatment - Hanawa, Takao (Frontiers in Bioengineering and Biotechnology, 2019)
Titanium (Ti) and its alloys are widely used for medical and dental implant devices — artificial joints, bone fixators, spinal fixators, dental implant, etc. — because they show excellent corrosion resistance and good hard-tissue compatibility (bone formation and bone bonding ability) among metals. Osseointegration is the first requirement of the interface structure between titanium and bone tissue. This concept of osseointegration was immediately spread to dental-materials researchers worldwide to show the advantages of titanium as an implant material compared with other metals. Since the concept of osseointegration was developed, the cause of osseointegration has been actively investigated. The surface chemical state, adsorption characteristic of protein, and bone tissue formation process have also been evaluated. To accelerate osseointegration, roughened and porous surfaces are effective. HA and TiO2 coatings prepared by plasma spray and an electrochemical technique, as well as alkalinization of the surface, are also effective to improve hard-tissue compatibility. Various immobilization techniques for biofunctional molecules have been developed for bone formation and prevention of platelet and bacteria adhesion. These techniques make it possible to apply Ti to a scaffold of tissue engineering. The elucidation of the mechanism of the excellent biocompatibility of Ti can provide a shorter way to develop optimal surfaces. This review should enhance the understanding of the properties and biocompatibility of Ti and highlight the significance of surface treatment.